Genetic diversity and differentiation of Pseudophoenix (Arecaceae) in Hispaniola. (27th October 2014) - Rodríguez‐Peña, Rosa A.; Jestrow, Brett; Meerow, Alan W.; Clase, Teodoro; Jiménez‐Rodríguez, Francisco; Griffith, M. Patrick; Santiago‐Valentín, Eugenio; Sustache‐Sustache, José A.; Francisco‐Ortega, Javier
<x xml:space="preserve">Abstract</x> Pseudophoenix ekmanii, P. lediniana and P. vinifera (Arecaceae) are endemic to Hispaniola. The more wide‐ranging P. sargentii also occurs on the island. Population genetic diversity and structure of Pseudophoenix was investigated using ten microsatellite loci. The study focused on populations from Hispaniola, but also included samples from other Caribbean islands. Results showed homozygote excess and high inbreeding coefficients in all populations across all polymorphic loci. Populations were highly differentiated. Results from both Bayesian and neighbour‐joining cluster analyses identified groups that were consistent with currently accepted species delimitations. We included the only known population of a possible undescribed taxon from the Dominican Republic. Results from the cluster analyses suggested that this putative taxon is closely related to P. sargentii from the Turks and Caicos Islands. There was no significant correlation between population size and observed heterozygosity. Contrary to what was anticipated, protected areas do not harbour most of the genetic diversity of the genus. The Haitian endemic P. lediniana should have the highest priority for conservation because it is restricted to a single population, it has a small number of individuals and it exhibited reduced levels of genetic diversity. The putative new taxon from the Dominican Republic has similar conservation concerns. Future conservation efforts should aim to maintain population connectivity and increase population size, particularly targeting populations with low genetic diversity. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 176, 469–485.